2x-3+x=3x+1

Simple and best practice solution for 2x-3+x=3x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-3+x=3x+1 equation:


Simplifying
2x + -3 + x = 3x + 1

Reorder the terms:
-3 + 2x + x = 3x + 1

Combine like terms: 2x + x = 3x
-3 + 3x = 3x + 1

Reorder the terms:
-3 + 3x = 1 + 3x

Add '-3x' to each side of the equation.
-3 + 3x + -3x = 1 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 + 0 = 1 + 3x + -3x
-3 = 1 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 = 1 + 0
-3 = 1

Solving
-3 = 1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -3(x-1)=2x+48 | | 5(x-7)+x=6(x-7)+7 | | x^2-16x=.35 | | 5(x-1)2x=2x-5 | | -7y+26=-3(y-6) | | X+11+x+14=17 | | 6n-3n+3120=5400 | | 8(-5b+7)+4b= | | 1250=50+30x | | p-49=5(p+3) | | -30-5n=-6(n+4) | | -135/-9=15 | | 10(s-6)=-149 | | 8x+11+3=23-7x+4 | | 5(v-3)=-9v-29 | | 44c+49=457c-7 | | 8(X-1)=-2x+52 | | 9(x+1.4)=18 | | -3(6x-8)+7=-18+31 | | 2(x+7)+6=2x+2 | | 7x=5(2x-5) | | 12(r-5)=60 | | -4-4p=24 | | 3x+1-1=3x+2 | | 20x(4-2)= | | 4(7v-8)=136 | | 8X+12Y=(X+Y) | | 2(y-5)=7y+8 | | 3y-2x=m | | N^2-81n=0 | | -9p-4=50 | | -8(n-1)=5-8n |

Equations solver categories